Evaluation of Different Nutrient Management Options for Soil Properties, Ground Water Quality and Factor Productivity of Basmati Rice (Oryza sativa L.) in Light Textured Soil - Kumar, Ashok; Kumar, Ankit; Dwivedi, Ashish; Shahi, U. P.; Naresh, R. K.; Kumar, Robin (International Journal of Bio-resource and Stress Management, 2016)
A four replicated field experiment was conducted during kharif season 2012 at Crop Research Centre of SVPUA & T Meerut, Uttar Pradesh to evaluate SSIPNMon scented rice.Findings revealed that customized fertilizer (TATA PARAS) recorded significantly maximum tiller, dry matter at 60 DAT, 1000 seed weight (24.26 g), grain yield (39.99 q ha-1), straw yield (63.73 q ha-1) and production efficiency (35.38 kg day-1 ha-1), besides average yield (39.99 q ha-1), yield increase (48.48%) and cost over control (67.30).Moreover, 66% of RDN+RDPK+34% N by Sesbania rostreta 0.9 t ha-1 not only resulted maximum protein (7.37%), protein yield (291.63 kg ha-1), milling (72.26%) and head rice recovery (52.18%) and minimum broken (6.54%) and LB ratio (4.25) but also fetches highest net profit (` 80161 ha-1), extra income over control (29302 Rs ha-1) and cost benefit ratio (1:4.3) besides, it was also improved aggregate stability (59.58%) and porosity (42.51%). Furthermore, control plot recorded highest BD (1.51 g cm-3), PD (2.39 g cm-3) and soil texture such as sand (47.94%) and silt (17.28%), whereas, clay (35.71%) was shown maximum under 66% of RDN+RDPK+34% N by vermicompost 1.25 t ha-1along with infiltration rate (0.17 cm hr-1) and hydraulic conductivity (0.74 cm hr-1), however soil texture class (clay loam) remained unaffected by various treatments. Moreover, ground water quality (BIS)viz., pH (6.5−8.5), EC (<0.7),Ca+++Mg++(<20 me L-1), Carbonate (<2.5 me L-1), Bicarbonate (<1.5 me L-1) and RSC (<1.25 me L-1) in terms of irrigation water during growing period at different stages was remained safe.Consequentlythere is an imperative need to discourage farmer practices and encouraging the SSIPNM in India.